2020
DOI: 10.1007/s13580-020-00280-4
|View full text |Cite
|
Sign up to set email alerts
|

Physiological traits associated with high temperature tolerance differ by fruit types and sizes in tomato (Solanum lycopersicum L.)

Abstract: Plants are very sensitive to environmental stresses, particularly to high temperature (HT) which is predicted to increase. This study was conducted to investigate the response to HT for identifying physiological traits associated with HT tolerance in tomato. Thirty-eight tomato accessions with three fruit sizes (cherry, medium and large) were grown in greenhouses where temperature set-point for ventilation was 25 °C and 40 °C for normal temperature (NT) and HT, respectively. HT increases plant height and stem … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
41
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(46 citation statements)
references
References 42 publications
5
41
0
Order By: Relevance
“…The Fla. lines which have large fruit size under the heat stress conditions could be more heat tolerant than other large-fruited lines. In fact, a recent finding revealed that tomato traits associated with heat tolerance depend on the fruit size [ 62 ].…”
Section: Discussionmentioning
confidence: 99%
“…The Fla. lines which have large fruit size under the heat stress conditions could be more heat tolerant than other large-fruited lines. In fact, a recent finding revealed that tomato traits associated with heat tolerance depend on the fruit size [ 62 ].…”
Section: Discussionmentioning
confidence: 99%
“…The importance of tomato plants in agricultural crops has certainly emerged. However, while reproductive tolerance during heat stress is an important value for the evaluation of tomato cultivars yield [13][14][15][16], tomatoes, in vegetative and reproductive stages, are sensitive to high temperature and have varying sensitivity to stress [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…The yield traits of tomatoes depending on the growth conditions are noticeably varied in one genotype [16]. Recently, multiple methods to screen for heat-tolerant tomato plants were validated at different growth stages under heat stress conditions [2][3][4]15]. The responses of different traits to the high temperature varied, and the results of correlation analysis showed the relationships between various traits (pollen viability, fruit set, flower number per inflorescence) within the control and heat-treated plants, but not between the two [14].…”
Section: Introductionmentioning
confidence: 99%
“…In the plants of pepper with different LHD signi cantly reduced both FS and NFR per plant regardless of cultivars. The fruit setting is the main indicator for screening the response of genotype on abiotic stress condition 1,5,32 , and heat stress may signi cantly reduce or increase the FS and number of owers 5,17,18,22 .…”
Section: Discussionmentioning
confidence: 99%
“…NFR can be used as predictor for FS in screening of the heat tolerant genotype since it positively correlates with FS in HT and that NT 16,18 . The plants of the cv.…”
Section: Discussionmentioning
confidence: 99%